Palladium-Catalyzed Anti-Markovnikov Oxidation of Aromatic and Aliphatic Alkenes to Terminal Acetals and Aldehydes - Ura, Yasuyuki (Synthesis, 2020)
Catalytic anti-Markovnikov (AM) oxidation of terminal alkenes can provide terminally oxyfunctionalized organic compounds. This short review mainly summarizes our recent progress on the Pd-catalyzed AM oxidations of aromatic and aliphatic terminal alkenes to give terminal acetals (oxidative acetalization) and aldehydes (Wacker-type oxidation), along with related reports. These reactions demonstrate the efficacy of the PdCl2(MeCN)2/CuCl/electron-deficient cyclic alkenes/O2 catalytic system. Notably, electron-deficient cyclic alkenes such as p-benzoquinones (BQs) and maleimides are key additives that facilitate nucleophilic attack of oxygen nucleophiles on coordinated terminal alkenes and enhance the AM selectivity. BQs also function to oxidize Pd(0) depending on the reaction conditions. Several other factors that improve the AM selectivity, such as the steric demand of the nucleophiles, slow substrate addition, and halogen-directing groups, are also discussed.1 Introduction2 Anti-Markovnikov Oxidation of Aromatic Alkenes to Terminal Acetals3 Anti-Markovnikov Oxidation of Aromatic Alkenes to Aldehydes4 Anti-Markovnikov Oxidation of Aliphatic Alkenes to Terminal Acetals5 Anti-Markovnikov Oxidation of Aliphatic Alkenes to Aldehydes6 Conclusion
Keywords: palladium; aromatic alkenes; aliphatic alkenes; anti-Markovnikov selectivity; oxidation; terminal acetals; aldehydes; electron-deficient cyclic alkenes